2009
DOI: 10.1186/1475-2840-8-47
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid supplementation normalizes the endothelial progenitor cell transcriptome of patients with type 1 diabetes: a case-control pilot study

Abstract: Background: Endothelial progenitor cells play an important role in vascular wall repair. Patients with type 1 diabetes have reduced levels of endothelial progenitor cells of which their functional capacity is impaired. Reduced nitric oxide bioavailability and increased oxidative stress play a role in endothelial progenitor cell dysfunction in these patients. Folic acid, a B-vitamin with anti-oxidant properties, may be able to improve endothelial progenitor cell function. In this study, we investigated the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 65 publications
1
23
1
Order By: Relevance
“…Therefore, we suggested that focused efforts should be invested to ensure that the dose of FA falls within the pharmacological range, especially in case of diabetic pregnancy (Capel and Corcoy, 2007). This result is inconsistent with that of the original study, which suggested that the gene expression profiles of EPCs from healthy controls and T1DM patients after FA treatment were very similar and that pairwise comparison showed no DEGs at an FDR of 0.05 (van Oostrom et al, 2009). We hypothesized that these differences may be due to the different method used for the analysis of microarray data.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Therefore, we suggested that focused efforts should be invested to ensure that the dose of FA falls within the pharmacological range, especially in case of diabetic pregnancy (Capel and Corcoy, 2007). This result is inconsistent with that of the original study, which suggested that the gene expression profiles of EPCs from healthy controls and T1DM patients after FA treatment were very similar and that pairwise comparison showed no DEGs at an FDR of 0.05 (van Oostrom et al, 2009). We hypothesized that these differences may be due to the different method used for the analysis of microarray data.…”
Section: Discussioncontrasting
confidence: 56%
“…This dataset was deposited by Oostrom (van Oostrom et al, 2009). EPC samples were collected from 20 patients with T1DM and 20 age-and gender-matched healthy control subjects.…”
Section: Microarray Datamentioning
confidence: 99%
“…Moreover, folic acid supplementation modulates EPCs transcriptome in diabetic subjects [43] . Fish oil intake, in a different study, revealed no significant effect on vascular health [44] , while a recent research showed beneficial actions a of fish-oil supplementation on cellular markers of endothelial function: increased numbers of EPCs and reduced numbers of EMPs (endothelial microparticles), thus favoring the maintenance of endothelial integrity [45] .…”
Section: Endothelial Health Maintenance: the Nutraceutical Approachmentioning
confidence: 99%
“…Id1 is a regulator of cellular proliferation and differentiation with its expression dysregulated in EPCs during disease [86]. For example, EPCs isolated from type-1 diabetic patients and patients with ovarian cancer have elevated expression of Id1 compared to healthy controls [87][88][89]. Moreover, in ovarian cancer this increase in Id1 has been linked with increased levels of integrin 4 (Table 1) and PI3K/Akt-induced EPC mobilisation, recruitment, and survival, likely contributors to the progression of the cancer [88,90].…”
Section: Inhibitor Of Dna-bindingmentioning
confidence: 99%